LITERARY TRANSLATION AND VARIED PERSPECTIVES IN LITERATURE - Kumar, Mahendra (International Journal of Research -GRANTHAALAYAH, 2025)
Translation Studies has become a well-established interdisciplinary research field that extends beyond purely linguistic concerns. The latter half of the twentieth century, in particular, saw the emergence of numerous theoretical contributions that laid the groundwork for Translation Studies as a distinct discipline. Translation has been perceived as both a reading and writing practice and as a medium for cultural exchange across the world. Various critical studies on translation theory explore different aspects related to the challenges and possibilities of translation as an academic pursuit. In recent years, the field has evolved with a growing focus on the translation of literary texts from multiple perspectives.